2023
DOI: 10.1590/1519-6984.249125
|View full text |Cite
|
Sign up to set email alerts
|

Gender-based incidence, recovery period, and mortality rate of COVID-19 among the population of district Attock, Pakistan

Abstract: COVID-19 is reported as an extremely contagious disease with common symptoms of fever, dry cough, sore throat, and tiredness. The published literature on incidence and gender-wise prevalence of COVID-19 is scarce in Pakistan. Therefore, the present study was designed to compare the distribution, incubation period and mortality rate of COVID-19 among the male and female population of district Attock. The data were collected between 01 April 2020 and 07 December 2020 from the population of district Attock, Pakis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
1
9
0
5
Order By: Relevance
“…[ 35 , 36 ] Finally, men have more comorbidities when compared to women, and have been shown to have a poor medical follow-up. [37] All these factors may lead to prolonged hospitalization, which may favor colonization by MDR bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…[ 35 , 36 ] Finally, men have more comorbidities when compared to women, and have been shown to have a poor medical follow-up. [37] All these factors may lead to prolonged hospitalization, which may favor colonization by MDR bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, males were associated with longer SOD (OR = 1.13, p < 0.001). However, a study in the district of Attock, Pakistan, found that males aged 40–60 had a significantly higher mortality rate than females [ 7 ]. Similarly, studies in India have shown that older people and younger males have a higher risk of death [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few studies discussing the epidemiological and clinical characteristics of patients and a few studies on vaccine doses and outcomes in Pakistan. The results showed that males had a higher incidence of disease and higher mortality rate [ 7 ] and that strict preventive measures for high-risk groups were essential [ 8 ]. Comorbidity, oxygen saturation, dyspnea on arrival, and length of hospital stay were also associated with a higher case fatality rate [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…COVID-19 is an acute respiratory infection caused by the SARS-CoV-2 coronavirus, potentially serious, of high transmissibility and global distribution (EJAZ et al, 2023). The first case of this type of coronavirus was registered on December 31, 2019, in the city of Wuhan, China (ALVES; DE SOUZA; CALÓ, 2021).…”
Section: Introductionmentioning
confidence: 99%